THE INFLUENCE OF MOTIVATION, WORK DISCIPLINE AND WORK ENVIRONMENT ON THE WORK PRODUCTIVITY OF PT PERKEBUNAN MINANGA OGAN EMPLOYEES IN THE REGIONAL OFFICE SECTION - Ratih Ratih; Faitullah Faitullah; Iin Hendrayani; Ahmad Muhammad Ridho (Jurnal Manajemen, 2024)
Abstract: Employee misconduct at PT Minanga Ogan Plantation is evident in the employees' tardiness and mishandling of break time. Additionally, employees' laziness, boredom, and lack of desire cause delays in their work. Increasing staff productivity requires more focus. This study aims to investigate the effects of work environment, work discipline, and motivation on worker productivity at the regional office of PT Minanga Ogan Plantation. 37 respondents made up the study's population, and questionnaire distribution was the method of data collection. Quantitative research methodologies are employed in this study. Descriptive and verification approaches were employed in data analysis techniques. The analysis in this study shows that, in the PT. Minanga Ogan Plantation Regional Office, work environment (X3) has no effect on productivity, whereas motivation (X1) and discipline (X2) each have an impact. At the PT Minanga Ogan Plantation Regional Office, motivation, work discipline, and work environment all contribute 64.9% to employee productivity, according to the coefficient of determination (R2) of 0.643. There are additional elements like pay, communication, and training that could affect the remaining 35.1%. To increase productivity, a comprehensive strategy that takes into consideration other variables influencing worker performance is required.